2020
DOI: 10.21203/rs.3.rs-25213/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CDR1as related miRNA-mRNA networks in differentiating goat skeletal muscle satellite cells

Abstract: Background: Myogenesis is a complex process controlled by several coding and non-coding RNAs (ncRNAs) such as circular RNAs (circRNAs) that well-known function as endogenous microRNAs (miRNAs) sponges. Over the past few years, numerous circRNAs have been known and their roles in biological processes have begun to be understood. Cerebellar Degeneration-Related protein 1 antisense (CDR1as), the most spotlighted circRNA as miR-7 sponge that has been blooming circRNAs’ research for a decade, and can potentially sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…has not yet been explored. circRNA CDR1as (cerebellar degeneration-related protein 1 antisense RNA, also termed as ciRS-7) is highly expressed during myogenesis and regulates muscle development [14][15][16] via serving as a competing RNA for muscle-related miRNAs, including miR-7, miR-206, and miR-671 [14,17]. Our previous research showed CDR1as/miR-7/insulin-like growth factor 1 (IGF1R) plays crucial roles in goat myogenesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…has not yet been explored. circRNA CDR1as (cerebellar degeneration-related protein 1 antisense RNA, also termed as ciRS-7) is highly expressed during myogenesis and regulates muscle development [14][15][16] via serving as a competing RNA for muscle-related miRNAs, including miR-7, miR-206, and miR-671 [14,17]. Our previous research showed CDR1as/miR-7/insulin-like growth factor 1 (IGF1R) plays crucial roles in goat myogenesis [14].…”
Section: Introductionmentioning
confidence: 99%